2022
DOI: 10.3390/sym14040787
|View full text |Cite
|
Sign up to set email alerts
|

Force, Power, and Morphology Asymmetries as Injury Risk Factors in Physically Active Men and Women

Abstract: This study aimed to investigate whether asymmetry of force, power, and tissue morphology are lower limbs (LL) injury risk factors in physically active adults. Fifty-eight men aged 23.8 ± 1.2 years and forty-seven women aged 23.3 ± 1.0 years were examined. Physical activity level was measured by the International Physical Activity Questionnaire, and injury data were collected with the Injury History Questionnaire. The countermovement jump was performed to evaluate force and power. LL tissue composition was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…Individuals with an abnormal spinal shape are more prone to injuries [ 31 ]. Asymmetry in skeletal muscle mass increases the risk of injury in physically active individuals [ 57 ]. Postural dysfunctions may contribute to functional impairments and hinder the execution of proper movement patterns [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with an abnormal spinal shape are more prone to injuries [ 31 ]. Asymmetry in skeletal muscle mass increases the risk of injury in physically active individuals [ 57 ]. Postural dysfunctions may contribute to functional impairments and hinder the execution of proper movement patterns [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that body composition indices might help establish the optimal value of BMI and FMI to achieve a positive effect in physical fitness improvement after HIIT. Generally, using a ROC curve method effectively describes the cut-off point indicating the phenomenon’s occurrence, e.g., injury risk or failure in a training program based on chosen factors such as physical fitness [ 28 , 29 ] and body composition indices [ 25 , 26 ]. However, there is a lack of observation considering body composition indices concerning blood pressure parameters.…”
Section: Discussionmentioning
confidence: 99%
“…All of that indices have recently gained significance, owing to several factors, including the similarity of its calculation method to that of BMI [ 23 ]. Their prognostic potential in detecting some phenomena, e.g., the risk of injuries, the risk of osteoporosis, or positive changes in physical efficiency, was positively verified [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three jump tests were performed by each participant. Three attempts were performed for each jump test, separated by a 60 s break [ 8 , 31 , 32 ]. The tests were performed in random order.…”
Section: Methodsmentioning
confidence: 99%
“…Jump performance is related to anaerobic, mixed, and aerobic disciplines [ 4 , 5 , 6 , 7 ]. Moreover, jump test measurements can help predict injury risk [ 8 ]. Therefore, jump tests are considered a universal tool for measuring physical performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%